Alterations in sperm DNA methylation, non-coding RNA expression, and histone retention mediate vinclozolin-induced epigenetic transgenerational inheritance of disease. Issue 2 (26th April 2018) - Ben Maamar, Millissia; Sadler-Riggleman, Ingrid; Beck, Daniel; McBirney, Margaux; Nilsson, Eric; Klukovich, Rachel; Xie, Yeming; Tang, Chong; Yan, Wei; Skinner, Michael K
Abstract: Epigenetic transgenerational inheritance of disease and phenotypic variation can be induced by several toxicants, such as vinclozolin. This phenomenon can involve DNA methylation, non-coding RNA (ncRNA) and histone retention, and/or modification in the germline (e.g. sperm). These different epigenetic marks are called epimutations and can transmit in part the transgenerational phenotypes. This study was designed to investigate the vinclozolin-induced concurrent alterations of a number of different epigenetic factors, including DNA methylation, ncRNA, and histone retention in rat sperm. Gestating females (F0 generation) were exposed transiently to vinclozolin during fetal gonadal development. The directly exposed F1 generation fetus, the directly exposed germline within the fetus that will generate the F2 generation, and the transgenerational F3 generation sperm were studied. DNA methylation and ncRNA were altered in each generation rat sperm with the direct exposure F1 and F2 generations being distinct from the F3 generation epimutations. Interestingly, an increased number of differential histone retention sites were found in the F3 generation vinclozolin sperm, but not in the F1 or F2 generations. All three different epimutation types were affected in the vinclozolin lineage transgenerational sperm (F3 generation). The direct exposure generations (F1 and F2) epigenetic alterations were distinct from the transgenerational sperm epimutations. The genomic features and gene pathways associated with the epimutations were investigated to help elucidate the integration of these different epigenetic processes. Our results show that the three different types of epimutations are involved and integrated in the mediation of the epigenetic transgenerational inheritance phenomenon.